积雪和有机质土对青藏高原冻土活动层的影响 (2013)
The most important factors affecting the active layer depth and distribution of permafrost on the plateau are snow cover and thickness of the organic soil layer,except for air temperature and solar radiation.In this study,data from two typical field sites(Binggou Station and Tanggula Station) on the plateau were used.The two stations were established by the CAREERI,CAS to monitor the impact of snow cover and organic soil layer on the energy balance and thermal state within the active layer.In order to find the process-based explanations for the recent monitoring results,the one-dimensional heat and water flow model CoupModel was used to calculate the vertical heat and water fluxes in a soil-snow-atmosphere system for climatic conditions at the two field sites.The model was successfully adjusted and applied to simulate the active layer dynamics under a surface covered by snow and tundra soil conditions. Subsequently,the model was used to investigate the effects of snow cover and organic soil layer on the active layer. The investigation on the influence of snow cover on the active layer at Binggou Station revealed that snow cover depth is the key to the effect of snow cover on the active layer.The shallow snow cover (less than 20cm)is advantageous to frozen soil development. The thick snow cover in winter obviously insulates the subsoil against energy losses to the atmosphere.The frozen active layer depth is reduced and not conducive to the conservation of permafrost.Sensitivity study shows that the thawing depth of the active layer decreases with organic increasing.The organic layer makes the underlying soil less responsive to solar radiation and air temperature fluctuations,owing to its low thermal conductivity and high heat capacity,and thus provides a protection against permafrost thawing. Both influences are of importance for the behavior of permafrost under global warming.